Association of Cardiovascular Risk Factors and Coronary Artery Lesion Among Coronary Artery Disease Patients - Koju, R; Humagain, S; Khanal, K (Kathmandu University Medical Journal, 2015)
Background Coronary artery disease (CAD) is associated with the numbers of risk factors causing coronary atherosclerosis. Coronary artery stenosis is mostly caused by coronary atherosclerosis.Objective This study aims to analyze the association between coronary artery stenosis and cardiovascular risk factors.Methods An observational study was conducted among CAD patients. The diagnostic coronary angiogram was performed from femoral approach using standard catheters and techniques to find out any abnormalities.Result A total 73 patients (44 male and 29 female) with coronary artery disease undergoing diagnostic coronary angiography was included with the documented cardiovascular risk factors. The coronary stenosis was found in 40 patients on the basis of stenosis grading. Among the established cardiovascular risk factors, sex, diabetes mellitus and smokers show are significantly associated with coronary stenosis among CAD patients. The present study shows the significant association of coronary stenosis among male CAD patients (OR 2.47; CI 0.94 – 6.48, p